Triggering DTH and CTL Activity by fd Filamentous Bacteriophages: Role of CD4+ T Cells in Memory Responses. (29th April 2010) - Del Pozzo, Giovanna; Mascolo, Dina; Sartorius, Rossella; Citro, Alessandra; Barba, Pasquale; D'Apice, Luciana; De Berardinis, Piergiuseppe
Abstract : The ability of fd bacteriophage particles to trigger different arms of the immune system has been previously shown by us with particular emphasis on the ability of phages to raise CTL responses in vitro and in vivo. Here we show that fd virions in the absence of adjuvants are able to evoke a DTH reaction mediated by antigen specific CD8+ T cells. In addition, we analyzed the induction of CTL responses in mice depleted of CD4+ T cells, and we observed that short-term secondary CTL responses were induced in the absence of CD4+ T cells while induction of long-term memory CTLs required the presence of CD4+ T lymphocytes. These results examine the cellular mechanism at the basis of fd efficiency and provide new elements to further validate the use of fd particles for eliciting and monitoring antigen-specific CTLs.